Isolated or integrated? Planning and management of urban renewal for historic areas in Old Beijing city, based on the association network system. (November 2019) - Liu, Zhao; Wang, Shunyi; Wang, Fang
Abstract: Against the backdrop of urban renewal and owing to functional segmentation, land resources in old cities are often trapped in an isolated management mode, causing ratcheting tensions in the human–land relationship. Therefore, the efficiency of land utilization and urban renewal suitability has attracted considerable attention. This study provides an urban renewal planning and management model to improve land-use efficiency and revitalize the old city via integrated development. Further, it seeks to strengthen system connectivity and network coordination of natural, social, and cultural resources in the old city and to propose a resource-sustainable development strategy of regionalization, cooperation, and differentiation for historic-area development. Based on the tracking data of tourism routes and the check-in data of tourists, and adopting a social network analysis and space syntax theory, the tourism network structure, node level, and network location are analyzed to differentiate the connections between area and node functions. Finally, an integrated network model of multi-group and multi-core hierarchical structures is proposed to strengthen the overall development. Based on the construction of a spatial network, from the perspective of supporting traffic network and land-resource spatial elements, similarities and differences between the status-quo land use and tourism development demand based on the association network system are compared to help promulgate management strategies for the land use of areas lacking attraction and supporting functions, which is conducive to land-use adjustment. The aim of this study is to provide a new view of the balance between resource sustainability, functional adaptability, and cultural continuation during the process of old-city renewal and to coordinate the relationship between urban conservation and renewal planning and industry development in historic areas. Graphical abstract: Image 1 Highlights: Protection of historic areas changes from single-block to integrated conservation. Land resources are not adapted to the integral development of tourism in the old city. Hierarchical multi-group and multi-core networks strengthen ties across areas. The central axis contributes to spatial tourism organization in old Beijing city.